Understanding the Impact of Liquid Organic Fertilisation and Associated Application Techniques on N2, N2O and CO2 Fluxes from Agricultural Soils - Balázs Grosz; Björn Kemmann; Stefan Burkart; Søren O. Petersen; Reinhard Well (Agriculture, 2022)
The prediction of liquid manure effects on N transformations in soils and the associated N2O and N2 fluxes is poor because previous investigations have mostly excluded N2. The objectives of this study were thus to quantify N2, N2O and CO2 fluxes, the source processes of N2O, N2O reduction and the depth distribution of moisture, NO3−, NH4+, water-extractable organic carbon concentration and pH in a laboratory incubation study with sandy arable soil using 15N tracing to quantify N processes and gaseous fluxes. The soil was amended with and without artificial slurry in various manure treatments (control, surface and injected) and incubated for 10 days at varying moisture levels, where the depth distribution of control parameters was determined twice during the experiment. Manure application was found to increase N2 and N2O fluxes from denitrification, with the highest fluxes occurring in the wet manure injection treatment (33 ± 32 mg N m−2 d−1 and 36.1 ± 39.1 mg N m−2 d−1, respectively), confirming that manure injection under wet conditions enhances denitrification and possibly also N2O fluxes. This study concluded that the current dataset is suitable as a first step towards improving the capability of biogeochemical models to predict manure application effects, but further studies with more soils and refined experiments are needed.